2019
DOI: 10.1021/acs.analchem.9b02686
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Trends in Nucleic Acid-Based Electrochemical Biosensors with Nanoporous Gold Electrodes

Abstract: Molecular diagnostics have significantly advanced the early detection of diseases, where electrochemical sensing of biomarkers has shown considerable promise. For a nucleic acid-based electrochemical sensor with signal-off behavior, the performance is evaluated by percent signal suppression (% ss), which indicates the change in current after hybridization. The % ss is generally due to more redox molecules (e.g., methylene blue) associating with the probe DNA bases in the single-strand form than the double-stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 73 publications
3
11
0
Order By: Relevance
“…On the contrary, the relative probe current displayed the opposite of the expected trend (Figure A), that is, initially a constant value followed by a rapid decrease for the samples with the largest EF (27.9 and 36.1). The amount of DNA desorbed from the samples with different EFs (Figure B) was in agreement with the amount of DNA recovered from each sample (∼10–50 ng/mL), as determined by our previous studies using the same grafting solution concentration (0.5 μM) . In those studies, we observed that the surface-bound and unbound DNA amounts strongly depended on the grafting solution concentration, where the recovered DNA probe approached 5000 ng/mL for grafting solution concentrations of 8 μM.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…On the contrary, the relative probe current displayed the opposite of the expected trend (Figure A), that is, initially a constant value followed by a rapid decrease for the samples with the largest EF (27.9 and 36.1). The amount of DNA desorbed from the samples with different EFs (Figure B) was in agreement with the amount of DNA recovered from each sample (∼10–50 ng/mL), as determined by our previous studies using the same grafting solution concentration (0.5 μM) . In those studies, we observed that the surface-bound and unbound DNA amounts strongly depended on the grafting solution concentration, where the recovered DNA probe approached 5000 ng/mL for grafting solution concentrations of 8 μM.…”
Section: Resultssupporting
confidence: 89%
“…Only a higher concentration gradient between the bulk and the pores, attained by high grafting solution concentrations, can drive DNA into the deeper pores. Figure C is a composite plot of electrochemical and fluorometric quantification of the DNA probe layer that illustrates the significant deviation from the expected linear relationship (shown with a trendline) between the two readouts. Taken together, the severely reduced efficiency in grafting the electrochemically active surface at higher EFs likely plays a role in the impaired sensor performance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the tunable morphology, np-Au exhibits other desirable features such as high surface area to volume ratio [ 36 ], electrical conductivity [ 37 ], biocompatibility [ 38 ], biofouling resilience [ 39 ], compatibility with conventional microfabrication processes [ 40 , 41 ], and facile surface functionalization via gold-thiol chemistry [ 42 ]. These benefits make np-Au an attractive material system for drug delivery [ 43 ], short nucleic acid detection [ 44 ], and catalysis [ 45 , 46 ]. Here, we report a computational and experimental study of in-plane molecular transport in np-Au thin films integrated into a microfluidic model of a reservoir distal to the pharmaceutical delivery site.…”
Section: Introductionmentioning
confidence: 99%